Folklor musical e identidad chilena en La Araucanía Tradición, Hegemonía y Modernidad (1860-1960) - Órdenes Delgado, Mathias (Ariadna Ediciones, 2023)
The book addresses the period that runs from the second half of the 19th century, when the State launched the process of territorial occupation of La Araucanía (1862-1883), until the end of the 1950s, in the years prior to the agrarian reform. It thus includes a long cycle in which the structural conditions did not allow the conflicts generated by land ownership and the colonization of La Araucanía to break out, leaving the hegemonic and identity conflicts generated in specific spaces of modernization and colonization moderately subdued. of the Mapuche territory.